Development and Validation of New Analytical Method for the Determination of Particle Size Distribution in Glimepiride Using Laser Based Particle Size Analyzer - S, Gosar A, Jadhav; V, Patil; S, Folane; A, Jadkar; T, Vispute (Edelweiss Applied Science and Technology, 2019)
Particle size is a key factor for modern drug quality since it affects the bioavailability and dissolution profile of the drug product. Study for Particle size is helpful to optimize drug product development process and improve the quality of drugs. In Order to determine the particle size of Glimepiride a novel and accurate Particle size determination method has been developed for the determination of particle size distribution of Glimepiride was described in this paper. This method has shown good reproducible results. By using water as dispersant wet method is developed and validated as per International conference on Harmonization guidelines (Q2 (R1)) and found out robust and reproducible with % RSD of d (10), d (50) and d (90) values found within acceptance limit ranges from 6.05% to 21.84% for d(0.1), 3.04% to 9.87% for d(0.5) and 4.69% to 14.32% for d(0.9) in validation. The described method is accurate and validated and successfully applied for the determination of particle size distribution of Glimepiride. Particle size method is discussed in detail to ensure in-depth understanding of particle size distribution and particle size method performance during lifetime of the product.